THE EFFECT OF DIGITAL ADVERTISING AND CELEBRITY ENDORSEMENT ON SALES PERFORMANCE ON SCARLETT WHITENING PRODUCTS - Haromain, Achmad; Rofifah, Lutfia; Muttaqjin, Imam (Universitas Muhammadiyah Tangerang, 2025)
The study aims to analyze the Influence of Digital Advertising (X1) Scarlett Whitening (X2), and on Sales Performance (Y) on Scarllet Whitening Products. This research is a quantitative research and a survey research. The sample taken in this study was 96 respondents using non-probability sampling techniques. The data analysis used in this study includes: descriptive statistical analysis, instrument analysis test, classical assumption test, italian statistical analysis test, multiple correlation test, determination coefficient test, partial test (t test), and simultaneous test (f test). ). The results of this study show that the Digital Advertising variable (X1), Scarlett Whitening (X2), simultaneously has a positive and significant effect on Sales Performance (Y) shown by the value of Fcal > Ftabel which is (117,746 > 3,094) with a significant value of 0.00 < 0.05.